Assessing Knowledge, Uptake and Factors associated with cervical cancer screening among women in selected communities of Wakiso district in Uganda: A population-based study - Robert M. Bulamba; Emmanuel Kyasanku; Fred Nalugoda; Alex Daama; James Nkale; Amanda Pearl Miller; William Byansi; Juliana Namutundu; Godfrey Kigozi; Grace Kigozi Nalwoga; Chris Balwanaki; Stephen Watya; et al. (PLoS ONE, 2025)
Background Uganda has the highest prevalence and incidence of cervical cancer in the East African region, with 80% of women diagnosed at advanced stage when survival is minimal. Literature on uptake of cervical cancer screening is limited in Uganda and thus womens’ knowledge and uptake of cervical cancer screening in the general population remains unknown. This study examined this gap of knowledge among women aged 25–65 years, across rural, urban and semi urban communities in a Ugandan district to inform design of targeted future cervical cancer screening programs in the country. Methods This descriptive cross-sectional study was conducted in Wakiso district, Uganda in May 2024 among 783 eligible women. Face-to-face interviews were conducted. Uptake of cervical cancer screening (outcome of interest) was dichotomously (yes/no) assessed. Knowledge of cervical cancer disease was assessed using the AWACAN validated tool, knowledge of cervical cancer screening was assessed using a set of ten (10) questions adapted from previous studies elsewhere, and all were measured on a Likert scale. Univariate, bivariate, and multivariable Poisson regression models with robust variance were performed using Stata software version 17. Results Respondents’ median age was 31 years (IQR 27–39 years). Majority (89.5%, 701/783) had heard of cervical cancer, and 90.6% (635/701) were aware of screening. Median knowledge score on signs and symptoms, risk factors and cervical cancer screening was 8.0 (IQR = 5–10), 8.0 (IQR = 5–11) and 7.0 (IQR = 4–10) respectively, and 54.3% had high knowledge about cervical cancer screening. Uptake of cervical cancer screening was 33.4%. Living in urban areas (aPR = 1.41, 95% CI: 1.05–1.88), being the ages 40–49 years (aPR = 1.76, 95% CI: 1.36–2.27), 50 years and above (APR = 2.16, 95% CI: 1.53–3.04), smoking (aPR = 1.39, 95% CI: 1.05–1.86), partner involvement (aPR = 2.61, 95% CI: 2.12–3.21), high knowledge about cervical cancer screening (aPR = 3.29, 95% CI: 2.35–4.60), and living with HIV (aPR = 1.66, 95% CI: 1.66–2.13) were significantly associated with higher uptake of cervical cancer screening among women in this setting. Conclusion Knowledge of cervical cancer screening was high, but the uptake of cervical cancer screening was lower than the recommended population coverage by WHO and Uganda national guidelines. There is need to improve accessibility to cervical cancer screening, increase nationwide cervical cancer awareness campaigns focusing on high-risk age groups and design targeted, tailored, culturally and socially sensitive interventions for young women aged 25–39 years to improve cervical cancer screening in Uganda.